Recipient Artery Rupture in Free Tissue Transfer in Heavily Radiated Beds. (23rd August 2013) - Howard, Brittany E.; Nagel, Thomas H.; Donald, Carrlene B.; Hayden, Richard E.
Abstract : Objectives: Report a patient series of microvascular arterial rupture in fibula free flap tissue transfer for osteoradionecrosis of the mandible. 1) Evaluate the risk factors for arterial anastomotic rupture in free tissue transfer. 2) Evaluate management strategies and outcomes of these rare cases. Methods: Retrospective review of the senior surgeon's experience at a tertiary referral center for reconstruction of mandibulectomy defects for osteoradionecrosis with free tissue transfer from 2004 through 2013. Data collection included oncologic history, surgical resection and reconstructive details, postoperative course, complications, and outcomes. Results: Over a 10‐year period 38 patients underwent free fibula osseocutaneous flap reconstruction for a diagnosis of osteoradionecrosis of the mandible. There was a prevalence of 11% (4/38) that suffered delayed rupture of the recipient artery proximal to the microvascular anastomosis. Histopathology of the anastomotic segment demonstrated acute arteritis with acute inflammatory cells and pseudoaneurysm formation of the native vessel. The recipient artery of the anastomosis was the facial artery in 3 cases and the internal maxillary artery in 1 case. Timing to initial rupture ranged from 7 to 17 (median 8.5) days. In 2 of the 4 cases the anastomosis was revised, only to suffer repeat rupture. Ultimately all anastomoses required ligation, timing ranging from 10 to 20 (mean 15) days. There was 100% flap survival. Conclusions: Recipient arterial rupture is a rare occurrence, and in our experience heavily radiated tissue is the greatest risk factor. If salvage anastomosis with the same artery is undertaken, a high risk for repeat rupture exists.